Perception for educational environment among medical students, Nainital: A Mixed method Cross-sectional study - Vishwakarma, Neetu; Thakkar, Hemaben Kanubhai; Awasthi, Sadhana (Indian Journal of Community Health, 2025)
Background- Environmental measurement has drawn some attention in the context of health professional education, with special focus on its effects on students outcomes. We sought to clarify the impact of CBME modules on the learning environment. An understanding of the educational program environment can help improve quality assurance. Aim and Objectives- To gain insight into medical students’ perception for Traditional and CBME curriculum for their educational environment in GMC Haldwani using DREEM Tool. To identify the strengths of current curriculum and suggestions for further improvement. Methodology- It is a mixed method Cross-sectional study conducted at Government Medical College Haldwani from November 2023-January 2024. In this study, the Dundee Ready Education Environment Measure (DREEM) tool was used for undergraduate medical students of traditional batch 2018 and CBME batch 2020. Scores obtained were expressed as mean ± Standard Deviation (SD). For qualitative part of the study, in depth interview of the 30 students of CBME Batch was conducted. Results- In quantitative part of the study ,we compared the DREEM scores of both the batches. The mean DREEM scores in this study were 120/200 for batch 2018 and 126/200 for batch 2020. Total scores were slightly high in CBME batch which means students of CBME batch were quite more satisfied with their learning environment. In qualitative part of the study we conducted in depth interviews with 30 randomly selected students from the CBME batch to understand the strengths of their curriculum and further ideas for improvement. Questions in the interview were asked under the domains of the DREEM tool. In qualitative part, reduction in duration of lectures and more research oriented teaching was suggested by the students. More student-centered activities like hospital visits and discussions of clinical scenarios were recommended. In social self perception, hostel rules to be relaxed more along with adding more of extra curricular activities were suggested. Conclusion- Both group of students had a positive perception of their learning environment, based on their scores. Through qualitative part of this study many strengths were perceived by the students of CBME curriculum along with the suggestions for further improvement.